2013
DOI: 10.1371/journal.pone.0067615
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Representation of Time in Schizophrenia Is Linked to Positive Symptoms and Cognitive Demand

Abstract: Time processing critically relies on the mesencephalic dopamine system and striato-prefrontal projections and has thus been suggested to play a key role in schizophrenia. Previous studies have provided evidence for an acceleration of the internal clock in schizophrenia that may be linked to dopaminergic pathology. The present study aimed to assess the relationship between altered time processing in schizophrenia and symptom manifestation in 22 patients and 22 controls. Subjects were required to estimate the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…In a recently published study, schizophrenic patients were found to underestimate anticipatory time intervals during the tracking of the movement of visual stimuli under cognitively challenging conditions (Peterburs et al, 2013). Common basis for the cognitive defect and impairment of interval timing in schizophrenia can be explained with the help of this model.…”
Section: Synopsis Of the Proposed Modular Clock Modelmentioning
confidence: 99%
“…In a recently published study, schizophrenic patients were found to underestimate anticipatory time intervals during the tracking of the movement of visual stimuli under cognitively challenging conditions (Peterburs et al, 2013). Common basis for the cognitive defect and impairment of interval timing in schizophrenia can be explained with the help of this model.…”
Section: Synopsis Of the Proposed Modular Clock Modelmentioning
confidence: 99%
“…It is widely accepted that GMV in certain cortical regions (including the frontal, temporal, and parietal cortices) is negatively correlated with hallucinations [ 44 , 49 52 ]. Since the reduction of prefrontal cortical volume and hallucinations are also associated with the susceptibility gene for schizophrenia and schizoaffective disorder, DISC1 [ 49 ], studies of the relationship between behavioral/cognitive deficits and hallucinations of schizophrenia are critical for understanding the pathopsychological processes and the endophenotype of this mental disorder [ 3 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, current neurocognitive and computational theories propose that the positive symptoms of schizophrenia are due to an abnormality in the brain's inference mechanism, such that a failure in the integration and exchange between incoming sensory information and expectations is related to the emergence of delusions and hallucinations ( Adams et al, 2013 ; Fletcher and Frith, 2009 ; Fuchs, 2007 ; Sterzer et al, 2016 ). Indeed, patients appear to have difficulty in predicting events over very short time intervals ( Giersch et al, 2016 ; Lalanne et al, 2012 ) and in efficiently coding events in time suggesting that prediction impairments in patients may concern the prediction of time in particular ( Giersch et al, 2015 ; Peterburs et al, 2013 ; Waters and Jablensky, 2009 ). Predictive timing disturbances in SZ have been mostly inferred from electrophysiological studies ( Todd et al, 2003 , Todd et al, 2008 ; Umbricht and Krljesb, 2005 ) although a recent behavioural investigation has established a link between predictive timing and clinical symptoms of SZ ( Martin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%